Preparation and mechanical characterisation of giant unilamellar vesicles by a microfluidic method - Karamdad,K; Law,RV; Seddon,JM; Brooks,NJ; Ces,O (Lab on a Chip, 2014)
Giant unilamellar vesicles (GUVs) have a wide range of applications in biology and synthetic biology. As a result, new approaches for constructing GUVs using microfluidic techniques are emerging but there are still significant shortcomings in the control of fundamental vesicle structural parameters such as size, lamellarity, membrane composition and internal contents. We have developed a novel microfluidic platform to generate compositionally-controlled GUVs. Water-in-oil (W/O) droplets formed in a lipid-containing oil flow are transferred across an oil- water interface, facilitating the self-assembly of a phospholipid bilayer. In addition, for the first time we have studied the mechanical properties of the resultant lipid bilayers of the microfluidic GUVs. Using fluctuation analysis we were able to calculate the values for bending rigidity of giant vesicles assembled on chip and demonstrate that these correlate strongly with those of traditional low throughput strategies such as electroformation.